2017
DOI: 10.1111/twec.12601
|View full text |Cite
|
Sign up to set email alerts
|

How do countries respond to anti‐dumping filings? Dispute settlement and retaliatory anti‐dumping

Abstract: Empirical studies have found that countries may respond strategically to the anti‐dumping petition filed against their exporters through their own retaliatory actions. Although most previous studies have focused on retaliatory anti‐dumping filings, in this paper we explore another potential avenue for strategic response—filing a complaint under the World Trade Organization's (WTO) dispute settlement understanding. Using a panel of global anti‐dumping filings between 1995 and 2011, we analyse under what conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…80 In response, China has stated that Article 56 has never been used; that this provision does not contradict the obligation under Article 17 of the ADA to have recourse to WTO dispute settlement instead of taking unilateral actions; and that, as a WTO Member it would resort to WTO dispute settlement before taking countermeasures. 81 While such countermeasures may be consistent with behaviour of other countries as documented by Feinberg and Reynolds (2018), such an explicit rule makes China more vulnerable to WTO challenges to their anti-dumping actions. Furthermore, the United States contends that China files tit-for-tat anti-dumping investigation against United States' companies whenever the United States brings a WTO dispute against China (Shaffer and Gao, 2017, p. 179).…”
Section: Criticism Against China's Anti-dumping Proceduresmentioning
confidence: 91%
“…80 In response, China has stated that Article 56 has never been used; that this provision does not contradict the obligation under Article 17 of the ADA to have recourse to WTO dispute settlement instead of taking unilateral actions; and that, as a WTO Member it would resort to WTO dispute settlement before taking countermeasures. 81 While such countermeasures may be consistent with behaviour of other countries as documented by Feinberg and Reynolds (2018), such an explicit rule makes China more vulnerable to WTO challenges to their anti-dumping actions. Furthermore, the United States contends that China files tit-for-tat anti-dumping investigation against United States' companies whenever the United States brings a WTO dispute against China (Shaffer and Gao, 2017, p. 179).…”
Section: Criticism Against China's Anti-dumping Proceduresmentioning
confidence: 91%
“…• Retaliatory Motives —The retaliatory motives literature implicates tit-for-tat trade dynamics as a primary determinant of gross antidumping petitions and measures imposed (Feinberg and Reynolds, 2018). To avoid mistakenly attributing changes in antidumping petitions filed to my primary explanatory variables, I include “Retaliation” to control for retaliatory dynamics.…”
Section: Independent Variablesmentioning
confidence: 99%
“… 21 Debapriya and Panda (2006); Feinberg and Reynolds (2006), (2018); Vandenbussche and Zanardi (2008, 93); Hartigan and Vandenbussche (2013); Upadhayay (2021). …”
mentioning
confidence: 99%
“…It is concluded that geographical distance cause less anti-dumping investigations against China, but increase of trade volume, GDP per capita, population, exchange rate, accession to WTO and financial crises rise the number of investigations. Feinberg and Reynolds (2018) examines global anti-dumping filings in post-WTO era about retaliation motives. The study evaluates the response of the targeted countries after an antidumping investigation whether to stay inactive, retaliate or take the case to WTO Dispute Settlement Mechanism (DSM).…”
Section: Literature Reviewmentioning
confidence: 99%